2022
DOI: 10.1108/nbri-06-2021-0041
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing customer satisfaction with chatbots: the influence of anthropomorphic communication styles and anthropomorphised roles

Abstract: Purpose Chatbots are increasingly used in online retail settings and are becoming a powerful tool for brands to engage customers. However, consumers’ satisfaction with these chatbots is mixed. Thus, this paper aims to investigate how using a social- versus task-oriented anthropomorphic communication style can improve customer satisfaction. Design/methodology/approach The authors explore the link between the anthropomorphic communication style use and customer perceptions/customer satisfaction in online custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Second, we divide the mind perception to FAIC into two dimensions, warmth and competence, based on the stereotype content model. Referring to the existing literature, some other divisions, such as cuteness/cool (Li et al, 2021) and servant/partner (Xu et al, 2022), could be applied to FAIC. We encourage researchers to explore these possibilities.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Second, we divide the mind perception to FAIC into two dimensions, warmth and competence, based on the stereotype content model. Referring to the existing literature, some other divisions, such as cuteness/cool (Li et al, 2021) and servant/partner (Xu et al, 2022), could be applied to FAIC. We encourage researchers to explore these possibilities.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Furthermore, chatbots have the ability to transform seller operations by streamlining business processes, automating complex tasks and enhancing customer service experience (Koehler, 2018), thereby providing considerable value to sellers (Kumar, 2016). For consumers, the anthropomorphic approach of chatbots can stimulate engagement, intellectual perception, collaboration and social interaction, fostering personal and emotional connections with customers (Keeling et al , 2010; Xu et al , 2022). Chatbots can also facilitate the move toward a “digital customer-company relationship” for e-commerce platforms (Steinhoff and Palmatier, 2020), and research has indicated that consumers appreciate extensive interactions with chatbots (Hill et al , 2015).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Recently, studies have found that brand image also has an impact on the country's image 9 , and the interaction of the brand image and the country's image may lead to the formation of deeper stereotypes, so how to reduce COO stereotypes becomes more and more important for developing countries in international competition. Previous studies and real-world examples have shown the advantages of anthropomorphism, when a brand adopts human-like language in communication, it may excite individuals' positive attitudes toward the producrt 10 , the latest research findings reveal the effects of anthropomorphism on customers' satisfaction 11 and product recommendations 12 . Psychological factors such as individuals' mindset could also influence their preference for products.…”
mentioning
confidence: 93%